The Contract or Agreement Business Law in Indonesia - Anirut Chuasanga (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
Agreement regulated in article 1313 of the Civil Code (KUH Perdata), namely